2018
DOI: 10.1038/s41598-018-23607-9
|View full text |Cite
|
Sign up to set email alerts
|

Systemic IGF-1 gene delivery by rAAV9 improves spontaneous autoimmune peripheral polyneuropathy (SAPP)

Abstract: Spontaneous autoimmune peripheral polyneuropathy (SAPP) is a mouse model of chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) in non-obese diabetic (NOD) mice null for costimulatory molecule, B7-2 gene (B7-2−/−). SAPP is a chronic progressive and multifocal inflammatory and demyelinating polyneuropathy of spontaneous onset with secondary axonal degeneration. Insulin-like growth factor 1(IGF-1) is a pleiotropic factor with neuroprotective, regenerative, and anti-inflammatory effects with extensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Female B7-2-null NOD mice (SAPP model) is considered the most representative model to study T-cell mediated inflammatory demyelinating nerve injury. We have characterized the clinical and pathological neuropathy temporally in these animals [16, 18]. The spontaneous inflammatory neuropathy starts in these animals around 20 weeks of age and the disease peaks around 32–35 weeks of age.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Female B7-2-null NOD mice (SAPP model) is considered the most representative model to study T-cell mediated inflammatory demyelinating nerve injury. We have characterized the clinical and pathological neuropathy temporally in these animals [16, 18]. The spontaneous inflammatory neuropathy starts in these animals around 20 weeks of age and the disease peaks around 32–35 weeks of age.…”
Section: Resultsmentioning
confidence: 99%
“…Each session consisted of three trials. The time that the mice stayed on the rod until falling was recorded, as described[16].…”
Section: Methodsmentioning
confidence: 99%
“…The beneficial effects of insulin, C-peptide and IGF-1 on neuropathy have been described, particularly for the treatment of diabetic polyneuropathy (48)(49)(50). Insulin is regarded as a nerve promotion factor that upregulates and stabilizes neuron filaments as well as tubulin in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…In STZ-induced rats, local unilateral administration of insulin to the sciatic nerve resulted in an increased number of small myelinated fibers and prevented slow nerve conduction in the treated nerve (26). Similarly, IGF-1, which is homologous to insulin and has partial common receptor affinity, can activate post-receptor signaling in neurons to ameliorate diabetic neuropathy (50). Binding of insulin/IGF-I to insulin receptor or IGF-I receptor activates autophosphorylation of the receptor and causes phosphorylation of several intracellular substrate proteins.…”
Section: Discussionmentioning
confidence: 99%
“…52 Additional neurological disorders associated with stroke are also influenced by IGF-1. Chronic fatigue and sleep dysfunction are commonly observed in patients following stroke 53 Studies in humans and animal models have shown that IGF-1 promotes a healthy sleep cycle, and is inversely associated with chronic fatigue (as reviewed by Chennaoui et al 54 ) Moreover, IGF-1 reduces neuropathic pain across several preclinical models, [55][56][57] suggesting IGF-1 may be advantageous for reducing post-stroke pain as well. This association has yet to be tested clinically or pre-clinically.…”
Section: Clinical Connections Between Igf-1 and Ischemic Strokementioning
confidence: 99%